Bovine Staphylococcus aureus: a European study of contagiousness and antimicrobial resistance - Nemati, Ghazal; Romanó, Alicia; Wahl, Fabian; Berger, Thomas; Rojo, Laura Vazquez; Graber, Hans Ulrich (Frontiers in Veterinary Science, 2023)
In dairy herds managements, mastitis is the leading cause of economic losses. One of the most important pathogens responsible for intra-mammary infections is Staphylococcus aureus. The genetic properties of S. aureus have a strong influence on its pathogenicity and contagiousness. In this study, we aimed to obtain a comprehensive overview of the key bovine S. aureus clinical properties, such as contagiousness and antimicrobial resistance, present in European strains. For this, 211 bovine S. aureus strains from ten European countries that were used in a previous study were used in this study. Contagiousness was assessed using qPCR for the detection of the marker gene adlb. Antimicrobial resistance was evaluated using a broth microdilution assay and mPCR for the detection of genes involved in penicillin resistance (blaI, blaR1, and blaZ). It was found that adlb was present in CC8/CLB strains; however, in Germany, it was found in CC97/CLI and in an unknown CC/CLR strains. CC705/CLC strains from all countries were found to be susceptible to all tested antibiotics. Major resistance to penicillin/ampicillin, chloramphenicol, clindamycin and tetracycline was detected. Resistance to oxacillin, trimethoprim/sulfamethoxazole and cephalosporins was rarely observed. In addition, contagiousness and antibiotic resistance seem to correlate with different CCs and genotypic clusters. Hence, it is recommended that multilocus sequence typing or genotyping be utilized as a clinical instrument to identify the most appropriate antibiotic to use in mastitis treatment. Actualization of the breakpoints of veterinary strains is necessary to address the existing antibiotic resistance of the bacteria involved in veterinary mastitis.